Does it matter if constitution-making is deliberative? - Welp, Yanina; Reuchamps, Min (Routledge, 2024)
Constitutions are the cornerstone of polities. They are fundamental in at least two senses. On the one hand, constitutions represent or are expected to represent the common agreements and values within a society. On the other hand, they organize the political, social, cultural, and economic relations in a given community. Paradoxically, constitutional replacements in democratic contexts, where to some extent the ideal conditions could be fulfilled, are the exceptions. Modern constitution-making started in the late eighteenth century. Elster describes seven waves of constitution-making across Europe and North America as well as in their former colonies throughout the world. Iceland and Ireland, that have been widely investigated in the literature will be discussed in an original fashion, are the flagship cases of such deliberative constitution-making. The chapter also presents an overview on the key concepts discussed in this book.